2021
DOI: 10.1155/2021/1828147
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Lauric–Myristic Acid/Expanded Graphite as Composite Phase Change Energy Storage Material

Abstract: Lauric acid (LA) and myristic acid (MA) were used to prepare a binary eutectic mixture. The expanded graphite (EG) was used as the carrier, and the lauric–myristic acid/expanded graphite (LA–MA/EG) composite phase change material was prepared by physical adsorption method. The microstructure, chemical structure, and thermal properties of LA–MA/EG were characterized by scanning electron microscopy (SEM), differential scanning calorimeter (DSC), Fourier transform infrared spectroscopy (FTIR), and thermal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Liu et al 42 evaluated the applicability of capric acid-stearic acid/EG CPCM in low-temperature energy storage and found that it has good TCU and stable thermal and chemical properties. Zhou et al 43 compounded a lauric acid-myristic acid binary eutectic mixture into EG by physical adsorption method to prepare LA-MA/EG with a phase transition temperature of 33.4 °C and enthalpy of 171.1 J/g. This material is suitable for applications in buildings to save energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 42 evaluated the applicability of capric acid-stearic acid/EG CPCM in low-temperature energy storage and found that it has good TCU and stable thermal and chemical properties. Zhou et al 43 compounded a lauric acid-myristic acid binary eutectic mixture into EG by physical adsorption method to prepare LA-MA/EG with a phase transition temperature of 33.4 °C and enthalpy of 171.1 J/g. This material is suitable for applications in buildings to save energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…33 Most studies focus on a few fatty acid binary eutectic mixture/expanded graphite (FABEM/EG) CPCMs, and systematic theoretical research and experimental characterization have not been carried out. In this paper, on the basis of our previous research, 23,34,35 10 FABEM/EG CPCMs were prepared by the physical adsorption method with fatty acid binary eutectic mixtures as PCMs and expanded graphite as the substrate material. The maximum absorption mass ratio (MaxAMR) of the FABEM in CPCMs is determined.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the shape-stability of PCM, a number of from-stable PCMs have been fabricated by impregnating PCM into porous substitute, such as expanded graphite [8][9][10][11], montmorillonite [12], calcium silicate [13], diatomite [14] and wood [15,16]. Wood with hierarchical and multi-porous structure, in recent years, has been used as a porous carrier for encapsulating PCM due to the low cost, free pollution and low carbon emission [17][18][19].…”
Section: Introductionmentioning
confidence: 99%